Evaluation of Phenolic Compounds, Antioxidant Activity and Bioaccessibility in Physalis Peruviana L - Guiné, Raquel P. F. (2020)
This work evaluated phenolic compounds in Physalis peruviana as well as their antioxidant activity and bioaccessibility, using an in vitro model of the gastrointestinal system. Three combinations of solvents were evaluated for the extraction of phenolic com- pounds. All other chemical components, their antioxidant activity and bioaccessibility were evaluated using established methods. P. peruviana is rich in fiber (4.61 g/100 g), vitamin C (26.70 mg/ 100 g), carotenoids (5.95 µg/100 g), total phenolic compounds (59.9 mgGAE/100 g), flavonoids (0.340 mgQE/10 g) and ortho- diphenols (94.6 mgGAE/100 g). The antioxidant activity varied from 7.7 to 13.7 µmolTE/g. The simulation of the digestive tract showed that only about 40-50% of the phenolic compounds remained available for intestinal absorption, and only 23 – 34% of the antioxidant activity was preserved after passing through the gastrointestinal system. Hence, these ratios have to be taken into consideration regarding the ingestion of phenolic com- pounds in order to expect desired health benefits for the human body, namely in terms of antioxidant activity.